2008
DOI: 10.1080/01443610802044908
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural impediments to male factor infertility evaluation in rural South-east Nigeria

Abstract: This study evaluated the rate and factors influencing male uptake of infertility investigations. Infertility constituted 11.2% of all new gynaecological consultations in the centre during the study period. A total of 61 (70.1%) males consented to seminal fluid studies without much hesitation, 12.4% after much persuasion, while the remainder (17.5%) refused. Obliging doctor's recommendation was the primary motivation for those who willingly had seminal fluid studies while the claim to be healthy and not being r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 1 publication
3
20
0
1
Order By: Relevance
“…The prevalence rate of male infertility in Nigeria is high, ranging from 20% to 25% (Anate & Akeredolu, ; Borokini, Clement, Dickson, & Edagbo, ; Nwabuisi & Onile, ). Institution‐based incidence of male infertility recently reported from some parts of Nigeria is 4.0%, 11.2% and 48.1% from llorin (north central), Abakaliki (south‐east) and Oshogbo (south‐west) respectively (Abiodun, Balogun, & Fawole, ; Adeyemi, Adekunle, & Afolabi, ; Umeora, Ejikeme, Sunday‐Adeoye, & Umeora, ). Owolabi, Fasubaa, and Ogunbiyi () noted a high rate of abnormal semen quality of male partners of infertile couples in Ile‐Ife, Osun State.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate of male infertility in Nigeria is high, ranging from 20% to 25% (Anate & Akeredolu, ; Borokini, Clement, Dickson, & Edagbo, ; Nwabuisi & Onile, ). Institution‐based incidence of male infertility recently reported from some parts of Nigeria is 4.0%, 11.2% and 48.1% from llorin (north central), Abakaliki (south‐east) and Oshogbo (south‐west) respectively (Abiodun, Balogun, & Fawole, ; Adeyemi, Adekunle, & Afolabi, ; Umeora, Ejikeme, Sunday‐Adeoye, & Umeora, ). Owolabi, Fasubaa, and Ogunbiyi () noted a high rate of abnormal semen quality of male partners of infertile couples in Ile‐Ife, Osun State.…”
Section: Introductionmentioning
confidence: 99%
“…The limited understanding of the mechanisms of human reproduction among people in these countries means that women are frequently held responsible for infertility and bear the social costs when conception does not occur and children are not born. 52 Umeora et al 53 found that, of 138 female consultations for infertility, only 63% of patients' husbands were ultimately prepared to attend the clinic. Of these, 17.5% were 'very reluctant and required much persuasion to undergo seminal fluid evaluation' and 12.6% refused.…”
Section: Psychological Reactions To Infertility Diagnosesmentioning
confidence: 99%
“…In some parts of this belt, infertility is said to constitute up to 65% of gynecological consultations [10]. Institution based incidence of infertility recently reported from some parts of Nigeria are: 4.0% [11], 11.2% [12] and 48.1% [13] respectively from llorin (North central), Abakaliki (south-east) and Oshogbo (South west).…”
Section: Introductionmentioning
confidence: 99%
“…While primary infertility is higher in other regions of the world, secondary infertility is more common in Africa [3]. In sub-Saharan Africa, pelvic infections largely constitute the cause of infertility in several places [9][10][11][12][13]. These stem from sexually transmitted diseases, post abortion and post-delivery complications.…”
Section: Introductionmentioning
confidence: 99%